Hadith #2354 - Sahih Muslim - Yasayr bin 'Amr (Sahih Muslim)
Did you hear the Messenger of Allah (ﷺ) making a mention of the Khawarij? He said: I heard him say (and he pointed with his hand towards the east) that these would be a people who would recite the Qur’an with their tongues and it would not go beyond their collar bones. They would pass clean through their religion just as the arrow passes through the prey.
Grade: Sahih